2018
DOI: 10.3233/jad-180241
|View full text |Cite
|
Sign up to set email alerts
|

A Small Molecule Inhibitor of Plasminogen Activator Inhibitor-1 Reduces Brain Amyloid-β Load and Improves Memory in an Animal Model of Alzheimer’s Disease

Abstract: Alzheimer's disease (AD) is a major cause of dementia in the elderly with no effective treatment. Accumulation of amyloid-β peptide (Aβ) in the brain is a pathological hallmark of AD and is believed to be a central disease-causing and disease-promoting event. In a previous study, we showed that deletion of plasminogen activator inhibitor 1 (PAI-1), a primary inhibitor of tissue type and urokinase type plasminogen activators (tPA and uPA), significantly reduced brain Aβ load in APP/PS1 mice, an animal model of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 51 publications
1
40
0
Order By: Relevance
“…The main consequences of the activation of this pathway are the opsonization of pathogens, the recruitment of inflammatory and immunocompetent cells, and the direct killing of pathogens . The association between levels of these analytes and A β burden has been noted in multiple previous studies . Among the other inflammatory analytes of significance in our results, the relationships between AD diagnosis and CCL2, MMP2, and VGEF have been previously reported, whereas VCAM1 has been reported in relation to both AD and vascular cognitive impairment …”
Section: Discussionsupporting
confidence: 78%
“…The main consequences of the activation of this pathway are the opsonization of pathogens, the recruitment of inflammatory and immunocompetent cells, and the direct killing of pathogens . The association between levels of these analytes and A β burden has been noted in multiple previous studies . Among the other inflammatory analytes of significance in our results, the relationships between AD diagnosis and CCL2, MMP2, and VGEF have been previously reported, whereas VCAM1 has been reported in relation to both AD and vascular cognitive impairment …”
Section: Discussionsupporting
confidence: 78%
“…Metabolic and vascular mechanisms have been suggested to contribute to MCI and dementia, yet the previous studies displayed discrepant results [33,34]. We explored the potential role of aberrant metabolism and vascular function in MCI by measuring plasma levels of promising markers, including PAI-1, C-peptide and VEGF-A.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent study has shown that administration of a PAI‐1 inhibitor for a period of 6 weeks reduces Aβ load in the hippocampus and cortex and improve learning and memory function in an AD mouse model . Notably, these effects were associated with increased tPA and plasmin activities.…”
Section: Diagnostic and Therapeutic Implications In Admentioning
confidence: 99%